Not all primary total hip arthroplasties are equal—so is there a difference in reimbursement? - Sodhi, Nipun; Dalton, Sarah E.; Garbarino, Luke J.; Gold, Peter A.; Piuzzi, Nicolas S.; Newman, Jared M.; Khlopas, Anton; Sultan, Assem A.; Chughtai, Morad; Mont, Michael A. (Annals of Translational Medicine, 2018)
Background: Relative value units (RVUs) are a physician reimbursement model based on the effort required, or value, in providing a procedure or service for a patient. Procedures such as conversion total hip arthroplasties (THAs) can be compared to primary THAs, but many studies have revealed increased difficulties in conversion cases. Despite the increased time and effort for conversion THA, it is unknown if this is reflected in the RVU compensation model. Therefore, the purpose of this study was to compare the: (I) mean operative times; (II) mean RVUs; (III) RVU/minute for primary and conversion THAs; and (IV) perform an individualized idealized surgeon annual cost difference analysis. Methods: A total of 103,702 primary THA patients were identified using CPT code 27130 and 2,986 conversion THA patients were identified using CPT code 27132 using the National Surgical Quality Improvement Program (NSQIP) database. The mean RVUs, operative times (minutes), and RVU/minute were calculated and compared. An annualize cost analysis of dollar amounts per case, day, and the year was also performed. Results: The mean operative times for the primary and conversion THA cohorts were 94 vs. 146 minutes (P